Descripción anátomo-funcional de un suicidio por consumo adictivo de inhalables, estudio de caso post-mortem - Charles Ysaacc Da Silva Rodrigues; Jorge Luís Olivares Peña; Paula Alexandra Carvalho de Figueiredo (Centros de Integración Juvenil A.C., 2019)
Introduction: the evidence mentions that the abuse of inhalants can cause alterations in the reuptake of dopamine, fundamentally in the mesolimbic system, the responsible structure of reward system and consequently of the addiction. Objective: the objective of the research was to investigate the relationship between the consumption of inhalants and suicide, through a retrospective post-mortem analysis. Method: the method used was a case study, with a qualitative approach of descriptive design, evaluated through the use of psychological autopsy and an in-depth interview, of the particular case of a suicide victim by hanging, of a 20-year-old male, consumer of inhalants. Results: thus, neuroanatomical alterations in the prefrontal cortex (ventromedial and orbitolateral), anterior cingulate cortex, basolateral nucleus of the amygdala, subthalamic nucleus and nucleus accumbens were verified, which, probably, could have had some influence on their suicidal behavior. Discussion and conclusion: altered structures directly and indirectly affect the mesolimbic system, and are related to low tolerance to failure, persistence in actions aimed at minimizing the results of social behaviors, ideation and magical thoughts in relation to their religious beliefs, and verbal disinhibition, which, probably, may have influenced on his suicidal behavior. ---------- Introducción: la evidencia menciona que el abuso de inhalables puede provocar alteraciones en la recaptación de dopamina, fundamentalmente en el sistema mesolímbico, estructura responsable por el sistema de recompensa y consecuentemente de la adicción. Objetivo: investigar la relación entre el consumo de inhalables y el suicidio, a través de un análisis retrospectivo post-mortem. Método: estudio de caso con enfoque cualitativo de diseño descriptivo, evaluado a través de autopsia psicológica y entrevista a profundidad de una víctima de suicidio por ahorcamiento de un joven de 20 años del sexo masculino, consumidor de pegamento. Resultados: se verificaron alteraciones neuroanatómicas en la corteza prefrontal (ventromedial y orbitolateral), corteza cingulada anterior, núcleo basolateral de la amígdala, núcleo subtalámico y núcleo accumbens. Discusión y conclusiones: las estructuras alteradas afectan directa e indirectamente el sistema mesolímbico y están relacionadas con baja tolerancia al fracaso, persistencia en acciones dirigidas a la minimización de los resultados de las conductas sociales, ideación y pensamientos mágicos con relación a sus creencias religiosas y desinhibición verbal, lo cual, probablemente, pudo influenciar en su conducta suicida.